Photodynamic therapy for treating infected skin wounds: A systematic review and meta-analysis from randomized clinical trials - de Oliveira, Analú Barros [UNESP]; Ferrisse, Túlio Morandin [UNESP]; Fontana, Carla Raquel [UNESP]; Basso, Fernanda Gonçalves; Brighenti, Fernanda Lourenção [UNESP] (Elsevier, 2022)
Background: Infected skin wounds represent a public health problem that effects 20 million people worldwide. Photodynamic therapy (PDT) is a treatment option with excellent results against several infections. Objective: This study aimed to perform a systematic review and meta-analysis on PDT efficacy for treating infected wounds based on randomized clinical trials (RCTs). Methods: PubMed, Scopus, Web of Science, SciELO, and the Cochrane library were searched. The Delphi List criteria and the Revised Cochrane risk-of-bias (Rob 2) were used for evaluating the quality of clinical trials. Meta-analyses were performed with the random-effect model. The odds ratio was the effect measure for binary outcomes, while the standard mean difference was used for continuous outcomes. The trim-and-fill method was used to detect small-study effects. The quality of evidence was verified for each outcome. Results: Only four out of 573 articles were selected for the qualitative and quantitative analyses. The most frequent cause of infected wounds was impaired venous circulation (75%). All studies used red LED light. PDT reduced healing time and improved the healing process and wound oxygenation. Patients treated with PDT showed 15% to 17% (p = 0.0003/ I2=0%) lower microbial cell viability in the wound and a significantly smaller wound size (0.72 cm2/p = 0.0187/I2=0%) than patients treated with placebo or red-light exposure. There was a high level of evidence for each meta-analysis outcome. Conclusion: PDT can be an excellent alternative treatment for infected skin wounds, though larger trials are needed.
Keywords: Infected skin wounds; Infection; Meta-analysis; Photodynamic therapy; Systematic review